Peningkatan Volume Penjualan Kopi Khas Sumbawa Melalui Penerapan Strategi Marketing Mix - Ana Merdekawaty; Fatmawati Fatmawati (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2023)
This study aims to determine and analyze the application of the marketing mix strategy, namely product, price, promotion and people to sales volume of typical Sumbawa coffee. This study uses a qualitative approach to data collection using interviews, observation and documentation. Triangulation of sources and techniques is used to test the validity of the data. The results showed that the typical Sumbawa coffee business had implemented a marketing mix strategy namely product, price, promotion and people and it turned out that this strategy could increase coffee sales volume. The application of these four variables has been carried out properly and is consistent with existing theory. These four variables play an important role in increasing sales volume, and high sales volume can increase business profits according to the expected target.